Critical Essays on Arthur Morrison and the East End - Maltz, Diana (Taylor & Francis, 2022)
In 1896, author Arthur Morrison gained notoriety for his bleak and violent A Child of the Jago, a slum novel that captured the desperate struggle to survive among London's poorest. When a reviewer accused Morrison of exaggerating the depravity of the neighborhood on which the Jago was based, he incited the era's most contentious public debate about the purpose of realism and the responsibilities of the novelist. In his self-defense and in his wider body of work, Morrison demonstrated not only his investments as a formal artist, but also his awareness of social questions. As the first critical essay collection on Arthur Morrison and the East End, this book assesses Morrison's contributions to late-Victorian culture, especially discourses around English working-class life. Chapters evaluate Morrison in the context of Victorian criminality, child welfare, disability, housing, professionalism, and slum photography. Morrison's works are also reexamined in the light of writings by Sir Walter Besant, Clementina Black, Charles Booth, Charles Dickens, George Gissing, and Margaret Harkness. This volume features an introduction and 11 chapters by preeminent and emerging scholars of the East End. They employ a variety of critical methodologies, drawing on their respective expertise in literature, history, art history, sociology, and geography. Critical Essays on Arthur Morrison and the East End throws fresh new light on this innovative novelist of poverty and urban life.